Climate, Land, Energy and Water System Nexus Optimization Modeling for Nepal - Bhandari, Hemanta; Darlami, Hari Bahadur; Jha, Ajay Kumar (Journal of Advanced College of Engineering and Management, 2023)
This paper introduces the amazing CLEWs Nepal model - a powerful tool that sheds light on the intricate interplay between climate policies and crucial resources like land, energy, and water. With more and more countries taking bold steps to combat climate change, it's crucial to understand the ripple effects of such decisions on other sectors. That's where CLEWs come in, providing decision-makers with valuable insights into the trade-offs and synergies involved in various climate policies. This paper examines the impact of the increasing global demand for power on greenhouse gas emissions, water usage, and hydropower production in Nepal. The study projects that by 2050, under current scenario and based on optimum growth rate, the country will only need to generate 9 GW of power, which can be mostly fulfilled by hydropower. However, there will be rise in CO2 emissions, particularly from the transport and biomass sectors. To mitigate the impact of this growth, the study recommends improving irrigated farming and forest conservation. The implementation of the Nationally Determined Contributions (NDC) can also contribute to reducing CO2 emissions and increasing hydropower production. We've calibrated the model to reveal fascinating insights into the long-term energy consumption patterns across different sectors, varying crop production based on irrigation levels, and total water usage in public and power sectors. And that's not all - we've also factored in the emissions produced while optimizing energy, food, and water demands for the public. Our model offers a range of policy options for Nepal, including an NDC scenario, which can help reduce CO2 emissions and preserve vital resources like water and land. We've also identified the costs and technology mix necessary to successfully implement these policies.